Depression, anxiety, and stress among first-year students and undergraduate students during the Covid-19 pandemic - Nurmina, Nurmina; Fahrianti, Fitri; Haryani, Meri; Wahyuni, Hera (International Journal of Research in Counseling and Education, 2021)
Stress and anxiety are becoming more common and prone to occur among first-year students who are undergoing the transition period from high school to university because new learning methods, when compared to undergraduate students will be more susceptible to depression due to the demands of completing a thesis. This research aims to difference in the level of stress, anxiety, depression of first-year and undergraduate students and differences in terms of gender at the Department of Psychology, Universitas Negeri Padang during the Covid-19 pandemic. This research is quantitative with a comparative study and obtained 592 respondents using stratified random sampling. Data collection of a Depression, Anxiety, Stress Scale (DASS-42). The data analysis techniques are carried out data analysis requirements with homogeneity and normality tests followed by hypothesis testing with t-tests. The result as for the depression variable there were significant differences with percentages in the level of first-year students and undergraduate students of 22.7% (mild) and 20.2% (extremely severe) respectively. The high prevalence in the first-year and undergraduate students of college life is alarming. It illustrates the need for primary and secondary prevention measures, with the development of adequate and appropriate support services for this group.